Gradenigo’s Syndrome with Lateral Venous Sinus Thrombosis - J Gordon Millichap (Pediatric Neurology Briefs)
A 4-year-old girl was admitted to the Department of Pediatrics, University of Chieti, Italy, with a 2-week history of fever and right otitis media, headache and vomiting.